Photo Guide to Birds of Costa Rica. - Garrigues, Richard (Cornell University Press, 2016)
Few ecosystem destinations are as abundant in their biodiversity as Costa Rica. Having the right field guides in hand can make all the difference when you're enjoying the country's birdlife. Photo Guide to Birds of Costa Rica, which features 549 excellent photographs, is designed to be equally useful for two distinct sets of readers. First are birders new to birding--or new to birding in Costa Rica--who want a guide to the birds that one is most likely to see, as well as to a few of the rarer species that one would hope to encounter. It treats more than 40 percent (365) of the species known from Costa Rica but is a guide to at least 75 percent of the birds commonly seen in a week or so of birding. The book will also be welcomed by experienced birders in search of a companion volume to The Birds of Costa Rica, second edition, an illustrated guide to all the birds of Costa Rica. The photographs in the species accounts in Photo Guide to Birds of Costa Rica are accompanied by names, measurements, field marks, habitat and behavior, voice, status and distribution, and range maps.